The redemptive spaces of storytelling in postcolonial literature. - Lim, Rebecca Sim Ming. (2014)
This thesis uses Walter Benjamin’s “The Storyteller” as an impulse to examine the redemptive spaces of storytelling in Abdulrazak Gurnah’s By the Sea, Preeta Samarasan’s Evening is the Whole Day and Michael Ondaatje’s Anil’s Ghost. In particular, I look at these authors’ representations of the workings of memory, time and space in response to the various forms of displacements, crises and traumatic encounters experienced by the characters within the texts. With reference to Robert Young’s formulation of postcolonialism as a field which is “directed towards the active transformation of the present out of the clutches of the past” (Young 4), this thesis traces the ways in which the form of storytelling has evolved and remains flexible to adapt or conform to the different needs of the storytellers in negotiating their relation with history. By reclaiming and integrating certain aspects of the oral tradition of storytelling into their narratives, I also suggest that these strategies enable the listener/reader to enter into and experience the world of the texts, thus forcing us to consider the way in which our different histories crisscross and provide openings for us to come into different forms of relations with each other. In other words, the act of storytelling redefines our relationship with different communities, even across transnational borders, cultures and time frames.